(untitled) (REMUNOM, 2025)
The study addresses tuberculosis (TB) as a transmissible and social disease linked to socioeconomic factors, with effective diagnosis and treatment but facing the challenge of treatment abandonment. Aiming to analyze factors associated with treatment abandonment of tuberculosis in Paraíba, the study used a descriptive and retrospective epidemiological methodology, analyzing data from the Notifiable Diseases Information System (SINAN) from 2019 to 2024, extracted from DATASUS-TABNET. Epidemiological profiles were discussed, including clinical form, sex, age group, and treatment status, highlighting the progressive increase in reported cases and abandonment, especially among men, young adults, and patients with pulmonary TB, the most prevalent and transmissible form. Results indicate abandonment is influenced by socioeconomic and behavioral factors, such as men’s lower health care and higher vulnerability of economically active young adults. The study emphasizes the importance of adherence to reduce hospitalizations, mortality, and drug resistance, reaffirming that abandonment compromises disease control and keeps the transmission chain active. It concludes that specific control strategies, including health education, active search, and social support, are essential to reduce abandonment and strengthen public adherence policies, consolidating tuberculosis control in the context of the Unified Health System (SUS) in Northeast Brazil. These data reinforce the need for continuous monitoring and qualification of health teams to face the care gaps shown by the study. The epidemiological scenario reports a trend of increased tuberculosis in Brazil, with challenges in meeting WHO global elimination targets, providing context for the relevance of the strategies pointed out in the research.